KADAR pH, KESADAHAN DAN BESI (Fe) PADA AIR SUMUR BOR DI SAMARINDA - Wahyu Alamsyah; Vita Pramaningsih; Marjan Wahyuni; Riza Miftahul Khair (EnviroScienteae, 2022)
Clean water is a human need for daily needs such as bathing, washing and toileting. In addition, clean water as a source of drinking water provided that it has been disinfected for example by cooking. The clean water quality must meet the requirements of Health Ministry Regulation No. 416 years 1990 to avoid health problems. Purpose of this study is analysis water quality of Drill Well Water for parameters pH, hardness and Iron (Fe)that used by residents in Samarinda especially on Jl. Gerilya, Gg. Sepakat, RT. 101. Research method used is field observation, taking drill well water samples and conducting analysis in the laboratory. Result of the study obtained that the levels of pH, hardness and Iron (Fe) in Drill Well Water obtained results for pH levels, namely samples A: 6.81, sample B: 6.87, sample C: 6.80, sample D: 6.66, and sample E: 6.28. Hardness level is sample A: 136 mg/L sample B: 114 mg/L sample C: 104 mg/L, D sample: 112 mg/L, and sample E: 298 mg/L and Iron content (Fe) sample A: 0.1389 mg/L, sample B: 0.1439 mg/L, sample C: 0.1464 mg/L, sample D: 0.1190 mg/L, and sample E 0.5608 mg/L. Base in the results, the drill well water used still meets the requirements.0000000000